Анализ эффективности теплообменников-утилизаторов теплоты энерготехнологических комплексов и агрегатов - Ганжа, Антон Николаевич; Заец, Елена Николаевна; Подкопай, Виктория Николаевна; Марченко, Наталья Андреевна (НТУ "ХПИ", 2016)
Созданы уточнённые математические модели, методики и алгоритмы для расчета и анализа сложных теплообменных аппаратов систем утилизации теплоты энерготехнологических процессов. Они дают возможность определить фактическую работоспособность рекуператоров на различных режимах с учетом факторов эксплуатации. Уточненные методы и средства позволяют повысить эффективность и ресурс рекуператоров, про-водить анализ их влияния на работу и технико-экономические показатели системы, уменьшить расходы топливно-энергетических и материальных ресурсов и негативное влияние высокотемпературных энерготехнологических процессов на окружающую среду.

Consideration was given to the influence produced by the distribution of the local intensities of heat exchange on the efficiency of heat exchangers with cross and mixed currents. Mathematical models, methods and algorithms were developed to calculate and analyze complicated heat exchangers designed for the heat recovery. Proposed methods give us an opportunity to define the actual functionality of the recuperators in different modes taking into consideration operation factors. Improved computing methods and tools allow us to extent the life of recuperators, analyze the influences produced on the functionality and engineering-and-economical performances of the system, reduce the consumption of fuel-energy resources and material resources and reduce the negative influence of high-temperature energotechnological processes on the environment. Developed models can be used in the future to solve optimization problems related to the design and improvement of the recuperators-recovery units.
Analysis of the efficiency of heat-exchangers – heat recovery units for energy technology systems and units
Keywords: теплообменные аппараты; энерготехнологические процессы; топливно-энергетические ресурсы; факторы эксплуатации; recuperator; operation factors; fuel-energy resources.